Brian Cherney in Conversation with Chris Paul Harman: Schulich School of Music, McGill University, 28 October 2017 - Harman, Chris (Intersections)

(untitled) (Canadian University Music Society / Société de musique des universités canadiennes, 2017)
In conversation with his McGill composition colleague Chris Paul Harman, Brian Cherney discusses his university education and his career as a composer, from his earliest works in the 1960s up to 2017.